A Supramolecular Wire Able to Self‐Assemble on Gold Surface: Controlling the Film Length to Optimize the Device Lifetime and Electron Transfer Efficiency - Sascha Kubitzky; Raffaella Lettieri; Elena Passaretti; Mariano Venanzi; Marta De Zotti; Claudia Mazzuca; Ernesto Placidi; Emanuela Gatto (Advanced Materials Interfaces)
Abstract A chemical “lego nanoset” has been used to realize different structures on gold surfaces. Three building blocks have been designed, in order to chemically link the surface and self‐assemble in an ordered manner. Self‐assembled films are arranged on a gold surface into 3D suprastructures via consecutive deposition of different mono‐layers, taken together by thymine‐adenine hydrogen bonds. Three films, composed of one, two, and three helical peptide layers, both containing a zinc‐tetraphenylporphyrin dye as an external sheet, are built and characterized by spectro‐electrochemical and spectroscopic techniques. All films are found to generate current under illumination, and their photoresponse and stability are studied as a function of the number of peptide layers. The efficiency of the photoconversion process has been correlated to the molecular organization of the porphyrin dyes in the film and to the templating role of the bridge between the porphyrin and the gold surface.